2021
DOI: 10.1101/2021.03.23.436677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species richness determinesC. difficileinvasion outcome in synthetic human gut communities

Abstract: Understanding the principles of colonization resistance of the gut microbiome to the pathogen Clostridioides difficile will enable the design of next generation defined bacterial therapeutics. We investigate the ecological principles of community resistance to C. difficile invasion using a diverse synthetic human gut microbiome. Our results show that species richness is a key determinant of C. difficile growth across a wide range of ecological contexts. Using a dynamic computational model, we demonstrate that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
(93 reference statements)
4
4
0
Order By: Relevance
“…In Data S2 , we show that species richness increases stability in the absence of spatial structure ( Figure S4 ; Table S1 ), which is consistent with previous work. 34 , 35 , 36 , 37 We also find that these designed communities are much less stable than the ones generated by the assembly scenario (median stability is 0.24 and 0.96, respectively, one-sided Wilcoxon rank-sum test: and ; Cliff’s delta is ), which is also consistent with recent findings. 23 , 26 Higher stability in the assembly scenario is due to higher species richness than in the design scenario ( Figures S5–S7 ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In Data S2 , we show that species richness increases stability in the absence of spatial structure ( Figure S4 ; Table S1 ), which is consistent with previous work. 34 , 35 , 36 , 37 We also find that these designed communities are much less stable than the ones generated by the assembly scenario (median stability is 0.24 and 0.96, respectively, one-sided Wilcoxon rank-sum test: and ; Cliff’s delta is ), which is also consistent with recent findings. 23 , 26 Higher stability in the assembly scenario is due to higher species richness than in the design scenario ( Figures S5–S7 ).…”
Section: Resultssupporting
confidence: 91%
“…Suppose we could increase the positive effects from the upstream to the downstream by increasing the upstream species richness. In that case, we can also expect that the upstream stability (i.e., the resistance to invasion upstream) increases as suggested by previous studies without spatial structure 35 , 36 , 37 (see also Data S2 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Interestingly, we found that the resident E. coli persists independently of microbiota diversity. This highlights the need to understand diversity at the strain level to predict key functions of the microbiome, such as its capacity to provide colonization resistance to opportunists (Hromada et al, 2021).…”
Section: Mainmentioning
confidence: 99%